The Correlation of Limestone Dust Exposure to Lung Function Impairment in Limestone Mining’s Workers, Centre Java, Indonesia - Utomo, Suyud Warno; Ni’mah, Zulfahtun; Asyary, Al (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Limestone dust is produced by limestone mining activities, one of them is PM2.5. Exposure of PM2.5 can cause lung function impairment. AIM: The purpose of this study was to determine the correlation exposure of PM2.5 with lung function impairment in workers. METHODS: This study used a cross-sectional study with total sampling technique of 30 workers. The instruments in this study used questionnaires for interviews, Dusttrak II TSI to measure PM2.5 concentration and spirometry to measure lung function. RESULTS: Based on the results of the study, the highest PM2.5 concentration values were 987 μg/m3 and the lowest were 14 μg/m3. The results of the analysis using Chi-square obtained a correlation between the use of personal protective equipment with lung function impairment (p = 0.000). Furthermore, the results using the Fisher’s exact test, there was a correlation between PM2.5 concentration and pulmonary function impairment (p = 0.002) and years of work with pulmonary function impairment (p = 0.000). CONCLUSION: Further research is needed using environmental health risk analysis to estimates based on intake.